Odpowiedzi

Najlepsza Odpowiedź!
2009-11-05T18:34:49+01:00
3x+2y=5 !*(-1)
2x+2y=2

-3x-2y=-5
2x+2y=2
-------
-x=-3!:(-1)
x=3

3*3-2y=-5
-2y=-5-9
-2y=-14!:(-2)
y=7

x=3
y=7


x+4y=11 !*(-2)
2x+5y=10

-2x-8y=-22
2x+5y=10

-3y=-12!:(-3)
y=4


x+4*4=11

x=11-16
x=-5

y=4
x=-5
2009-11-05T18:37:41+01:00
A) {3x+2y=5 I *(-1) 2x+2y=2}
{-3x-2y=-5 2x+2y=2}
-x=-3 I*(-1)
x=3
{x=3 2*3+2y=2}
{x=3 2y=-4} I/2
{x=3 y=-2}
b) { x+4y=11 I*(-2) 2x+5y=10}
{-2x-8y=-22 2x+5y=10}
-3y=-12 I/(-3)
y=4
{y=4 2x+5*4=10}
{y=4 2x=-10} I/2
{y=4 x=-5}